Karakteristik Membran Selulosa Triasetat Yang Diprepasi Secara Inversi Fasa Presipitasi Imersi - Sofyana Sofyana; Sri Aprilia; Mulkus Assaki (Universitas Syiah Kuala, 2020)
Phase inversion is the most versatile technique which to prepare membranes that is microfiltration, ultrafiltration, nanofiltration and reverse osmosis. In the phase inversion technique in immersion precipitation, the membrane structure formed is affected by the type of solvent and the membrane structure will affect the performance. During the process of precipitation homogeneous polymer will form a solid comprising two parts of a non-porous dense layers layer forming a dense layer on the membrane surface and a porous structure forming a support layer at the bottom in this case an asymmetric structure formed membrane. This research was conducted in 2 stages of activity. First membrane manufacturing process with phase inversion method of cellulose triacetate 18% concentration,dimentyl sulfoxide solvent 82%, 75 oC anneling temperature and 1 minute evaporation time. The changing variables are the operating pressure of 1, 2, 3, 4, 5, 6, 7 bar, the composition of the solvent (dimentyl sulfoxide): solvent (Water) = (0 : 10) is referred to as the M1 membrane and (2 : 8 ) is referred to as the M2 membrane. Membranes that have been made in the characteristics of permeability values and cloud point. The result showed that membrane M1 has permeability value 2,0588 L / m.h.bar, M2 membrane has permeability value 0,9009 L/m2.h.bar. Cloud point point was reached in dope solution with coagulation bath 0: 10 after addition of solvent: non-solvent which is 1,870 gram, while point cloud point at dope solution with 2: 8 coagulation tube was reached in addition of solvent: non-solvent is 6,602 gram.